2013
DOI: 10.1104/pp.113.230714
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA156: A Potential Graft-Transmissible MicroRNA That Modulates Plant Architecture and Tuberization in Solanum tuberosum ssp. andigena        

Abstract: MicroRNA156 (miR156) functions in maintaining the juvenile phase in plants. However, the mobility of this microRNA has not been demonstrated. So far, only three microRNAs, miR399, miR395, and miR172, have been shown to be mobile. We demonstrate here that miR156 is a potential graft-transmissible signal that affects plant architecture and tuberization in potato (Solanum tuberosum). Under tuber-noninductive (long-day) conditions, miR156 shows higher abundance in leaves and stems, whereas an increase in abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
195
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 254 publications
(228 citation statements)
references
References 79 publications
13
195
1
4
Order By: Relevance
“…EMSA has been broadly used for characterization of core promoter elements in both animals (Morachis et al, 2010;reviewed in Roy and Singer, 2015) and plants (Achard et al, 2003), including characterization of miRNA core promoters (reviewed in Xie et al, 2010). Using gel-shift assays, Bhogale et al (2014) identified binding sites for the SQUAMOSA PROMOTER BINDING-LIKE9 (SPL9) TF in the potato (Solanum tuberosum) miR172 promoter. Predictably, these binding sites contained a GTAC motif resembling SPL9 binding sites in the promoters of protein coding genes.…”
Section: Techniques That Bash Promoter Bashing: Tf Binding Validationmentioning
confidence: 99%
“…EMSA has been broadly used for characterization of core promoter elements in both animals (Morachis et al, 2010;reviewed in Roy and Singer, 2015) and plants (Achard et al, 2003), including characterization of miRNA core promoters (reviewed in Xie et al, 2010). Using gel-shift assays, Bhogale et al (2014) identified binding sites for the SQUAMOSA PROMOTER BINDING-LIKE9 (SPL9) TF in the potato (Solanum tuberosum) miR172 promoter. Predictably, these binding sites contained a GTAC motif resembling SPL9 binding sites in the promoters of protein coding genes.…”
Section: Techniques That Bash Promoter Bashing: Tf Binding Validationmentioning
confidence: 99%
“…Because of the transport capacity of the tuber signal, the search for the activating signal has focused on primary products like microRNAs, fulllength mRNAs, and less abundant proteins that move through the sieve element system of the plant (Table I). Two important microRNAs, miR172 and miR156, have been implicated in potato development, but their exact mechanistic connection to tuber formation has not been established conclusively (Martin et al, 2009;Bhogale et al, 2014).…”
mentioning
confidence: 99%
“…Для секвенирования используют как экспериментальные подходы, связанные с высокопроизводительным секвени рованием (Zhang et al, 2013), так и биоинформатические подходы для предсказания структуры микроРНК по уже известным последовательностям (Zhang et al, 2009). Ис следования направлены на изучение микроРНК, которые регулируют экспрессию конкретных генов (Chi et al, 2015), участвующих в формировании стрессового ответа на засуху (Zhang et al, 2014) и играющих роль в процессе клубнеобразования (Martin et al, 2009;Bhogale et al, 2014;Lakhotia et al, 2014).…”
Section: идентификация микрорнк участвующих в регуляции физиологичесunclassified